Forecasting the northern African dust outbreak towards Europe in April 2011: a model intercomparison [Discussion paper] - Huneeus, Nicolas; Basart, Sara; Fiedler, Stephanie; Morcrette, ‪Jean-Jacques; Benedetti, Angela; Mulcahy, Jane; Terradellas, Enric; Pérez García-Pando, Carlos; Pejanovic, Goran; Nickovic, Slodoban; Schulz, Michael; Cuevas Agulló, Emilio; et al. (European Geosciences Union, 2015)
In the framework of the World Meteorological Organisation's Sand and Dust Storm Warning Advisory and Assessment System, we evaluated the predictions of five state-of-the-art dust forecast models during an intense Saharan dust outbreak affecting Western and Northern Europe in April 2011. We assessed the capacity of the models to predict the evolution of the dust cloud with lead-times of up to 72 h using observations of aerosol optical depth (AOD) from the Aerosol Robotic Network (AERONET) and the Moderate Resolution Imaging Spectroradiometer (MODIS), and dust surface concentrations from a ground-based measurement network. The authors acknowledge AERONET (http://aeronet.gsfc.nasa.gov) and thank the PIs of the AERONET stations used in this paper for maintaining the observation program and the AERONET-Europe TNA (EU-ACTRIS grant no. 262254) for contributing to calibration efforts. S. Basart acknowledges the Catalan Government (BE-DGR-2012) as well as the CICYT project (CGL2010-19652 and CGL2013-46736) and Severo Ochoa (SEV-2011-00067) programme of the Spanish Government. Stephanie Fiedler acknowledges the funding of the European Research Council through the starting grant of Peter Knippertz (no. 257543). Nicolas Huneeus acknowledges FONDAP 15110009 and FONDECYT 1150873. The database on dust concentrations at ground level was produced in the framework of the Grant Agreement LIFE10 ENV/IT/327 from the LIFE Programme of the European Commission. J. Pey has been partially funded by a Ramon y Cajal Grant (RYC-2013-14159) from the Spanish Ministry of Economy and Competitiveness. Carlos Pérez García-Pando acknowledges the Department of Energy (DE-SC0006713) and the NASA Modeling, Analysis and Prediction Program. The work was partly funded within MACC-II by the European Commission under the EU Seventh Research Framework Programme, contract number 283576 and MACC-III by the European Community’s Horizon 2020 Programme under grant agreement no. 633080.